Chronic Kidney Disease and Mortality in Implantable Cardioverter-Defibrillator Recipients - Aamir Cheema; Tejwant Singh; Manreet Kanwar; Karuna Chilukuri; Viqar Maria; Fareena Saleem; Katrina Johnson; John Frank; Luis Pires; Sohail Hassan (Cardiology Research and Practice)
Incidence of sudden cardiac death (SCD) in end-stage renal disease (ESRD) remains high. Limited data is available about whether implantable cardioverter-defibrillators (ICDs) can prevent arrhythmic death in patients with chronic kidney disease (CKD). The purpose of this retrospective study was to determine the impact of CKD on all-cause and sudden cardiac death in ICD recipients. We evaluated 441 consecutive patients who underwent ICD implantation at our center between 1994 and 2002. We found that mortality rate was higher in patients with eGFR <60 mL/min and those with ESRD on hemodialysis (43%, n=69/162 and 54%, n=12/22, resp.) than in patients with eGFR ≥60 mL/min (23%, n=58/257; P<.0005). The SCD rate was also higher in the patients with ESRD (50%) than in CKD patients not on dialysis (10.2%; P<.0005). Mortality rate for single-chamber ICDs was 56.8% in comparison with dual-chamber ICDs (38.1%) and for biventricular ICDs (5.0%) (P<.0005).